Paleoclimate reconstruction of the last 36 kyr based on branched glycerol dialkyl glycerol tetraethers in the Padul palaeolake record (Sierra Nevada, southern Iberian Peninsula). (1st April 2022) - Rodrigo-Gámiz, Marta; García-Alix, Antonio; Jiménez-Moreno, Gonzalo; Ramos-Román, María J.; Camuera, Jon; Toney, Jaime L.; Sachse, Dirk; Anderson, R. Scott; Sinninghe Damsté, Jaap S.
Abstract: Quantitative continental climate reconstructions covering the last glacial cycle from the Iberian Peninsula are scarce. In order to fill this gap, we obtained for the first time a high-resolution mean annual air temperature (MAAT) record based on the distribution of specific bacterial membrane lipids (i.e., branched glycerol dialkyl glycerol tetraethers; brGDGTs) from the last 36.0–4.7 kyr palaeolake record recovered by the Padul-15-05 sedimentary core (Padul, Sierra Nevada, southern Iberia). The fractional abundance of the three major groups of GDGTs present in the Padul sediments, GDGT-0, crenarchaeol and the summed brGDGTs, is comparable with that of other shallow and small (<10 km 2 ) European lakes. Despite variations in the lithology in the studied section, the GDGT composition remains relatively stable, except for the uppermost 116 cm of the record, representing the ephemeral/emerged lake stage, which is characterized by higher crenarchaeol fractional abundances. The identification of a specific brGDGT that has only been detected in anoxic lakes provides evidence for in-situ brGDGT production in the water column and/or sediments in the Padul palaeolake. Its presence/absence probably denotes a succession of periods with a variable oxygen content in the bottom waters of the palaeolake. MAAT was reconstructed based on the distribution of brGDGTs using an African lake calibration and ranged between 12 and 20 °C. A new Bayesian calibration to mean temperature of Months Above Freezing (MAF) depicts similar temperature variations with a mean absolute difference of 0.7 °C. The MAAT reconstruction in the Padul palaeolake for the 36.0–4.7 kyr period reveals similarities with climate variability described at high-latitudes and in the westernmost Mediterranean area during this interval, showing cold conditions during the last three Heinrich Stadials and the Younger Dryas and warm conditions during the Dansgaard–Oeschger interstadials (7–1) and the Bölling-Alleröd period. Despite the more stable and warm general climate conditions during the Early and Mid-Holocene, rapid centennial-scale temperature changes are registered in the Padul palaeolake in good agreement with variations observed in the Mediterranean forest record. Highlights: The brGDGTs distribution in the Padul record is comparable to small European lakes. The presence of the brGDGT IIIa'' is evident for in-situ brGDGT production in Padul. Reconstructed continental mean annual air temperature (36.0–4.7 kyr) ranged from 12 to 20 °C. The temperature record shows Dansgaard–Oeschger interstadials and Heinrich stadials.